Barriers to Quitting Smoking Among Young Adults: The Role of Socioeconomic Status. Issue 2 (February 2018) - Carlson, Samantha; Widome, Rachel; Fabian, Lindsey; Luo, Xianghua; Forster, Jean
Purpose: The aims of this analysis were to explore how self-reported barriers to quitting vary by socioeconomic status (SES) among young-adult smokers and to assess their relationship to quitting. Design: This analysis uses 2 waves of telephone-survey data from the Minnesota Adolescent Community Cohort study. Setting: Midwestern United States. Participants: Participants (n = 419) were smokers aged 17 to 24 years. Measures: Socioeconomic status was estimated using the highest level of education completed by the participants' parents. Demographics, smoking behavior, and perceived barriers to quitting were collected via survey questions. Analysis: Differences in barriers by SES were assessed using prevalence ratios (PRs). Relative risks were calculated to assess the association between barriers and quitting status 1 year later, testing for effect modification by SES. Results: Compared to the high SES group (n = 314), the low SES group (n = 105) was more likely to report several barriers to quitting; however, only the risk of gaining weight was significantly more common (PR: 1.38 [1.05-1.83]). There were no significant associations between barriers and quitting status 1 year later, but the number of cigarettes per day was consistently related to the likelihood of quitting 1 year later, regardless of SES. Conclusion: Despite the limited generalizability to racially diverse populations and different geographic locations, the results suggest perceived barriers may not differ by SES or predict quitting among young adults; however, nicotine dependence may play an important role.